O17.4 Impact of the human papillomavirus immunization program on rates of anogenital warts in british columbia, canada 2000–2017. (14th July 2019) - Lukac, Christine; Donken, Robine; Otterstatter, Michael; Mazo, Olga; Wong, Stanley; Marra, Fawziah; Smith, Laurie; Naus, Monika; Money, Deborah; Krajden, Mel; Grennan, Troy; Gilbert, Mark; et al.
Abstract : Background: In 2008, British Columbia (BC), Canada, implemented a provincially-funded school-based quadrivalent human papillomavirus (HPV-4) vaccine program for girls born in 1994 or later. In 2015, the program was expanded to include men who have sex with men (MSM) born in 1989 or later. To determine the impact of the vaccine on anogenital warts (AGW), diagnosis rates were measured among women who have sex with men (WSM), men who have sex with women (MSW), and MSM. Methods: AGW diagnoses were ascertained from an electronic medical record system used at 16 geographically dispersed high volume sexually transmitted infection (STI) clinics across BC. Clients aged 14–46 years, born between 1970–1999 who accessed services from 2000–2017 were included. Rates were calculated as new AGW diagnoses over person-years (PY) at risk, and stratified by age group, period of clinic visit, and birth cohort. Age-period-cohort Poisson modeling produced adjusted relative rates (aRR). Results: There were 204, 832 clinic visits by 85, 158 unique individuals: 28, 366 (33%) WSM, 35, 688 (42%) MSW and 14, 534 (17%) MSM. After adjusting for age and period, overall AGW rates were 56% lower among the birth cohorts 1994–1996 compared to 1991–1993 (1.21 vs 2.72 cases/100PY, aRR: 0.44, 95%CI: 0.34, 0.59). AGW rates in the 1994–1996 cohort were 65% lower among WSM (0.97 vs 2.77 cases/100PY, aRR: 0.35, 95%CI: 0.22, 0.57), 58% lower among MSW (1.60 vs 3.78 cases/100PY, aRR: 0.42, 95%CI: 0.28, 0.65) and 41% lower among MSM (1.14 vs 1.19 cases/100PY, aRR: 0.59, 95%CI: 0.38, 0.91) versus the 1991–1993 cohort. Conclusion: The HPV-4 vaccine program had a significant impact on lowering AGW rates in BC, specifically among WSM born after 1994 who had access to the school-based program, and MSW born after 1994 likely from herd immunity. A smaller reduction in AGW rates among MSM may reflect delayed access to provincially-funded HPV-4 vaccine. Disclosure: No significant relationships.